SIFAT-SIFAT KOPI INSTAN GULA KELAPA DARI BERBAGAI RASIO KOPI ROBUSTA-ARABIKA DAN GULA KELAPA-GULA PASIR - Yhulia Praptiningsih; . Tamtarini; . Ismawati; Sari Wijayanti (Faculty of Agricultural Technology, University of Jember, 2012)
Indonesian coffee consumption per capita increase every year, it was 6-8%. Now, Indonesian coffee consumption is 800 g/capita/year. They like of instant coffee and three in one coffee, because this coffee was very simple and easier to prepare. The Robusta coffee has higher of yielded, nevertheless the Arabica coffee has good flavor. Generally, the crystallization step of instant coffee processing conducted by cane sugar adding. Coconut palm sugar has good flavor, but the crystallization step would be difficulty when used on instant coffee processing, because the sucrose content of coconut palm sugar lower than cane sugar. The aim of this research was to obtain the appropriate of Robusta-Arabica coffee ratio and coconut palm sugar-cane sugar ratio to produce the coconut palm sugar instant coffee which has good properties and good preference. Based on this research, the best treatment was Robusta-Arabica coffee ratio 1-2 and coconut palm sugar-cane sugar ratio 30-70.Keywords: instant coffee, robusta coffee, arabica coffee, coconut palm sugar, cane sugar